2013
DOI: 10.1002/ajmg.a.36042
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for the V37I GJB2 mutation in fifteen probands with mild to moderate sensorineural hearing impairment: Further confirmation of pathogenicity and haplotype analysis in Asian populations

Abstract: Hearing impairment affects 1 in 650 newborns, making it the most common congenital sensory impairment. Autosomal recessive nonsyndromic sensorineural hearing impairment (ARNSHI) comprises 80% of familial hearing impairment cases. Mutations in GJB2 account for a significant number of ARNSHI (and up to 50% of documented recessive (e.g. more than 1 affected sibling) hearing impairment in some populations). Mutations in the GJB2 gene are amongst the most common causes of hearing impairment in populations of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Some studies indicated that the p.Val37Ile and p.Met34Thr missense variants were benign polymorphisms [ 3 , 23 ]. Results of other studies supported their pathogenicity and implicated their association with a mild-to-moderate hearing impairment [ 1 , 24 , 25 ]. We detected one compound c.35delG and p.Val37Ile heterozygous individual with a severe prelingual hearing disorder.…”
Section: Discussionmentioning
confidence: 56%
“…Some studies indicated that the p.Val37Ile and p.Met34Thr missense variants were benign polymorphisms [ 3 , 23 ]. Results of other studies supported their pathogenicity and implicated their association with a mild-to-moderate hearing impairment [ 1 , 24 , 25 ]. We detected one compound c.35delG and p.Val37Ile heterozygous individual with a severe prelingual hearing disorder.…”
Section: Discussionmentioning
confidence: 56%
“…[ 37 ] At present, the pathogenicity of this mutation site is controversial, because some individuals with normal hearing also carry the homozygous mutation. [ 38 , 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm our earlier reported data on the high prevalence of the c.-23+1G>A pathogenic variant among the Yakut population in Eastern Siberia [ 84 ]. Interestingly, in the Yakut patients, the second most common pathogenic variant was c.109G>A (p.Val37Ile), which was found with high frequency in Southeast Asia (Thailand, Indonesia, Malaysia) [ 41 , 47 , 48 ], East Asia (China, Korea, Japan) [ 33 , 35 38 , 40 , 42 , 44 , 46 ], and Australia [ 71 ], as well as among patients with HI of Asian origin in the US [ 87 ]. Pathogenic variants с.35delG (22.34%), c.-23+1G>A (5.31%), and c.313_326del14 (2.12%) were the most frequent in the group of Russian patients.…”
Section: Discussionmentioning
confidence: 99%